One health: a structured review and commentary on trends and themes - Helen Louise Brown; Isabella Grace Pursley; Daniel L. Horton; Roberto M. La Ragione (BMC, 2024)
Abstract Background One Health (OH) is defined as a unifying approach aiming to sustainably balance and optimise the health of people, animals and the ecosystem. It recognises that the health of humans, animals (both domestic and wild), plants and the wider ecosystem are both interdependent and linked. As a concept, it aims to address complex problems requiring input from multiple disciplines. Suitable issues for OH approaches typically include global issues which can widely impact not only the health of humans and animals, but also have a significant environmental impact. Examples include emerging zoonotic diseases and antimicrobial resistance (AMR). Interpretations and use of the term OH differ in the literature and have the potential to dilute its impact. The meaning of OH among the research community has evolved over time. Here, we collate the OH relevant literature from the last two decades, identifying major themes and trends and considering how OH has been embraced differently across various geographical regions. Methods and results Bibliographic databases were searched using the term "One Health" AND ("Veterinary" OR "Animal") AND ("Medicine" OR "Human") AND ("Environment" OR "Ecosystem") during the period between 1980 and 2022. Data analysis and narrative synthesis identified themes, similarities, and differences within literature. Web of Science and PubMed returned 948 and 1250 results for the period mentioned above. The predominant literature focused on human health, with veterinary health second, although often to benefit human health. It was found that OH is often utilised as a public health approach, generally towards the end of disease surveillance and control. Interestingly, while authors from low- and middle-income countries were well-represented within studies using the term OH, they were less well-represented as corresponding authors. Conclusions The predominant focus of the literature was on human and veterinary health, implying OH approach is human-orientated, despite its suggestion that all domains share a common 'health'. Potential improvement to OH could be achieved through greater incorporation of the environmental and social sciences for a more encompassing approach.